Liquidity risk underlying debt financing and economic condition: A Panel data analysis of Islamic Bank in Malaysia - Hidthiir, Mohamad Helmi; Bahari, Zakaria; Mat Junoh, Mohd Zukime; Abdul Manaf, Arman Hadi; Abdullah, Muhammad Safizal; Ab Halim, Mohd Suberi (Leena and Luna International, Chikusei, Japan., 2017)
The objective of this paper is to analyze the determinants of Islamic bank liquidity risk in Malaysia with special focus on debt financing. Based on this objective, this study utilized unbalanced panel dataset of 17 Islamic banks in Malaysia over the period 1998-2012.The method use is this study is panel data regression analysis. The results show that the level of capital is significant with the liquidity risk.For debt financing variable, the results signify that the higher volatility of debt financing modes will cause some liquidity risk.For macroeconomic condition, the result shows that impact of inflation rate could decrease the nominal value deposits in Islamic bank and finally the relationship of liquidity risk and Islamic bank deposit rate is negative.The implication of this study is that when the Islamic banks consider on their liquidity risk management, the have to look upon the behaviour of debt financing, inflation rate and Islamic bank deposit rate.